The construction of sequencing model in FTMSK course management system / Salehuddin Shuib, Suhardi Hamid, Shamsul Jamel Elias - Shuib, Salehuddin; Hamid, Suhardi; Elias, Shamsul Jamel (Institute of Research Management & Innovation (IRMI), 2010)
The research focuses on sequencing structure of Learning Content Management System (LCMS). The aim of the research is to construct the sequencing model of Course Management System of FTMSK (CMS-FTMSK) as well as to compare several approaches in modelling sequencing. SCORM Sequencing Model is used while constructing the sequencing model for CMS-FTMSK. This research will deliver the most reliable model and methodology that can be adopted and applied by authors in order to implement a systematic learning content. Henceforth, the selected model will be used to construct the sequencing model of Course Management System for the Faculty of Information Technology and Quantitative Sciences (FTMSK) which is a proposed automated system that will create, store, assemble and deliver personalized e-learning content. The researchers have found out that the objectives of the research have been achieved by constructing the sequencing model for Course Management System of FTMSK based on the SCORM Sequencing Model. A few benefits have been highlighted which include providing a better understanding on how the sequencing structure a system behaves.